The price of racial reconciliation - Walters, Ronald W. (Politics of race and ethnicity., 2008)
Presents the conceptual difficulties involved in the project of racial reconciliation by a comparative analysis of South African Truth and Reconciliation and the demand for Reparations in the United States.